Universal and Risk Factor Based Screening for Gestational Diabetes in Hospital Raja Permaisuri Bainun. a prospective cohort study - Sinnasamy, Chandran (Universiti Sains Malaysia, 2011)
Diabetes Mellitus is major public health and economic problem of global significance, responsible for significant mortality and morbidity among general population. Prevalence of diabetes continues to rise and increasingly affects individuals of all ages, including young adults, children and women of childbearing age that who are at increased risk of diabetes during pregnancy and the rate is expected to go higher in the foreseeable future. The World Health Organization (WHO) has estimated that in 2030, Malaysia would have a total number of 3 million diabetics compare to 0.94 million in 2000. In concordance with this, the prevalence of Gestational Diabetes Mellitus is increasing as well. The mean prevalence of GDM lies between 3% and 5% with an upper boundary of 14%. GDM represents the most common metabolic complication of pregnancy, and is associated with maternal (pre-eclampsia, hypertension, caesarean section) and fetal morbidity (macrosomia, birth trauma, hypoglycaemia, hyperbilirubinemia, hypocalcemia, respiratory distress syndrome). The aim of the study is to determine the fetomaternal outcomes in GDM mothers (antenatally, intrapartum and postpartum) and to compare the adverse outcome between GCT negative, GCT false positive and GDM mothers. This is a prospective cohort study carried out in the Obstetrics and Gynaecology Department, Hospital Ipoh from June 2009 to January 2010. All pregnant women attending Antenatal clinic at Hospital Permaisuri Bainun were included into the study once they fulfill the inclusion criteria. Once enrolled the progress of the pregnancy was followed up until delivery. All the recruited mother were subjected to 50g oral Glucose Challenge Test (OGCT) regardless to fasting state. 1-h venous plasma glucose concentration of >7.2mmol/l was arbitrarily considered as a positive screening result. Patients with a positive OGCT subsequently underwent a 75 g 2-h OGTT, which was considered as the actual diagnostic test for GDM. In addition, women with risk factors (negative GCT) for GDM also underwent a 75 g OGTT regardless of the result of OGCT. In this study, GDM was diagnosed if either or both of fasting plasma glucose is >5.6 mmol/L or two-hour plasma glucose is >7.8 mmol according to WHO guideline. The various maternal and fetal outcomes were compiled with the help of a questionnaire. All the data entry and analysis were carried out using the social science and statistical packaged (SPSS) version 12. A p value of less than 0.05 was considered statistically significant. Number of patients enrolled into this study was 992. The main bulk of the study population was Malays (46%) but when the highest prevalence of GDM analysed individually was seen among Chinese (25%). Majority of the study group in GDM category were multiparous (88.8%) and moderate obesity (BMI range 26 -29). There were strong association between obesity and incidence of GDM (p = <0.001). Using a multivariate analysis even after adjusted for the possible confounders the following adjusted odds ratio (OR) and 95% confidence interval (CI)] incidence of polyhydramnios (OR : 4.21 ;95% CI: 2.43 - 7.31), incidence of PPROM ( OR : 3.21 ;95% CI: 1.89 - 5.47 ), incidence of preterm labour (OR 3.99 ;95% CI: 2.53 - 6.30 ), incidence of Gestational hypertension (OR : 2.09 ;95% CI: 1.31 - 3.34 ), incidence of caesarean delivery ( OR : 3.80 ;95% CI: 2.63 - 5.49 ), incidence of instrumental delivery ( OR : 3.49 ;95% CI: 1.69 - 7.20 ), incidence of macrosomic baby ( OR : 1.80 ;95% CI: 1.02 - 3.19), incidence of shoulder dystocia (OR : 5.60 ;95% CI: 1.67 - 18.77 ), incidence of extended perineal tears( OR : 3.60 ;95% CI: 1.32 -9.78 ). Where else among the GCTfalse positive mothers incidence of PPROM ( OR : 2.03 ;95% CI: 1.08 - 3.84 ), incidence of caesarean delivery ( ;95% CI: 2.51 -5.58 ), OR: 3.74 incidence of macrosomic babies ( OR : 2.15 ;95%CI: 1.19-3.88 ), extended perineal tears ( OR : 5.82 ;95% CI: 2.22 - 15.27 ). There were no significant differences were noted in following aspects like pre-eclampsia, babies bom with low APGAR score ( <6 in 5 min),cord blood pH, delayed discharge from ward following LSCS. There were also noted trends of adverse fetomaternal outcome among the patients with false positive GCT. Gestational Diabetes Mellitus is an independent risk factor for a number of adverse obstetric outcomes; in our population 50 g OGCT appears to identify a higher number of GDM than risk factor based screening. Combined with risk factor screening a few more cases of GDM would be found.GCT false positive mothers had an increased like hood of an adverse pregnancy outcome as well.